The role of traditional sports in maintaining and preserving regional culture facing the era of society 5.0 - Dedi Nofrizal; Liliana Puspa Sari; Pangondian Hotliber Purba; Esty Setyo Utaminingsih; Anggri Dwi Nata; Devi Catur Winata; Muhammad Syaleh; Ahmad Al Munawar; Edi Kurniawan; Rahmat Permana; Wiwik Yunitaningrum; Fitria Meilina; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The Indonesian archipelago is a vast country that stretches from Sabang to Marauke and consists of many islands. One of the largest and most diverse countries in the world is Indonesia. This includes a variety of cultures and sports that have been around for a long time. Among the traditional sports followed by the people of Riau Province are Traditional sports are part of the Grand Design of Indonesian National Sports, based on the Presidential Regulation of the Republic of Indonesia (Perpres RI) Number 86 of 2021 sports must be able to develop the physical, spiritual, and socio-cultural potential of the community as a manifestation of the values of Pancasila. Riau Province has traditional sports, such as Pacu Jalur, Pacu Sampam Leper, and Tual Sago which are unique and interesting. The method used in this research is qualitative research. The research subjects were ten people, including local government, stakeholders, community activists, and observers of traditional sports in Riau Province. Data were collected through observation, in-depth interviews, and documentation. The data obtained were analyzed qualitatively with the following steps: (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusion drawing. The results of the study are as follows: 1) The recognition of the community, youth, and government towards traditional sports is extraordinary, this is evidenced by the number of people who know and recognize the existence of traditional sports. 2) Revitalization is carried out by forming good management to strengthen the existence of traditional sports and organizing traditional sports events. 3) Promotion or introduction of traditional sports is done by disseminating information about traditional sports events to various conventional and digital media to local communities and migrants. 4) Conservation or maintaining and preserving regional culture by holding annual traditional sports events and festivals, teaching the younger generation, and archiving traditional sports. 5) Education towards Traditional sports are often used as a means to teach social values, such as cooperation, discipline, and sportsmanship. It can also be a medium for socialization between generations. 6) Digital technology allows traditional sports to gain international recognition and introduce local cultures to a global audience. It can also facilitate wider cultural exchange in the face of the era of Society 5.0.